Kraj jako marka handlowa - Raftowicz-Filipkiewicz, Magdalena (Wydawnictwo Uniwersytetu Wrocławskiego, 2007)
The article explores the issue of national brands, pointing out its manifestations and possible benefits it can bring, treated as commercial brands, to a country on the global market. It presents also a historical context of branding national and a country brand equity. The author proves that creating a strong national brand could enhance a country position in the international area. Because of that reason it should be cared about national branding and a brand’s image of the country.
Keywords: marka; narodowości; konkurencyjność; marka narodowa